2021
DOI: 10.1101/2021.07.16.452674
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The context of experienced sensory discrepancies shapes multisensory integration and recalibration differently

Abstract: Whether two sensory cues interact during perceptual judgments depends on their immediate properties, but as suggested by Bayesian models, also on the observer's a priori belief that these originate from a common source. While in many experiments this a priori belief is considered fixed, in real life it must adapt to the momentary context or environment. To understand the adaptive nature of human multisensory perception we investigated the context-sensitivity of spatial judgements in a ventriloquism paradigm. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…Despite the hand and computer cursor moving in different spatial planes, both signals are perceptually combined and the presentation of visually rotated feedback engages the processes of multisensory integration (Ladwig et al, 2013; Rand and Heuer, 2013; Debats et al, 2017b; Kirsch and Kunde, 2019, 2022), multisensory recalibration(Rand and Heuer, 2019b), and motor adaptation (Krakauer et al, 2000; Bock et al, 2003; Debats et al, 2023). In fact, the properties of multisensory integration and recalibration seen in this visuo‐motor paradigm are analogous to those observed in purely perceptual paradigms such as the audio‐visual ventriloquism effect and aftereffect (Chen and Vroomen, 2013; Bruns, 2019; Park and Kayser, 2022). The likely reason for the perceptual combination of visual and proprioceptive signals in the visuo‐motor paradigm is that the spatially discrepant felt movements of the hand and seen movements of the cursor are temporally correlated in the same way as felt and seen movements of our hand.…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…Despite the hand and computer cursor moving in different spatial planes, both signals are perceptually combined and the presentation of visually rotated feedback engages the processes of multisensory integration (Ladwig et al, 2013; Rand and Heuer, 2013; Debats et al, 2017b; Kirsch and Kunde, 2019, 2022), multisensory recalibration(Rand and Heuer, 2019b), and motor adaptation (Krakauer et al, 2000; Bock et al, 2003; Debats et al, 2023). In fact, the properties of multisensory integration and recalibration seen in this visuo‐motor paradigm are analogous to those observed in purely perceptual paradigms such as the audio‐visual ventriloquism effect and aftereffect (Chen and Vroomen, 2013; Bruns, 2019; Park and Kayser, 2022). The likely reason for the perceptual combination of visual and proprioceptive signals in the visuo‐motor paradigm is that the spatially discrepant felt movements of the hand and seen movements of the cursor are temporally correlated in the same way as felt and seen movements of our hand.…”
Section: Introductionsupporting
confidence: 61%
“…Multisensory integration is known to be sensitive to the overall experimental context in which it is probed, and the bias observed in particular trials can depend on the nature of preceding trials in an experiment (Gau and Noppeney, 2016; Rand and Heuer, 2018; Rohe et al, 2019). For example, with a larger range of intermodal discrepancies we observed weaker integration in the visuo‐motor task (Debats et al, 2023), but stronger integration in an audio‐visual ventriloquism paradigm (Park and Kayser, 2022). In line with such a context dependency of integration we have previously observed that prolonged exposure to constant discrepancies between hand movements and visual feedback reduces the integration bias (Rand and Heuer, 2020).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Most datasets analysed here have been published previously, though there are three exceptions (see Table 1 for details). Overall the data are from 11 experiments, all of which were designed to probe the ventriloquism effect and the immediate ventriloquism aftereffect following an established design (Wozny and Shams, 2011) that we have used in a number of previous studies (Park and Kayser, 2019, 2020, 2021; Park et al, 2021; Park and Kayser, 2022). Participants were adult volunteers who reported no history of neurological diseases, normal vision and hearing.…”
Section: Methodsmentioning
confidence: 99%
“…We analysed data from 10 experiments, eight of which have been published previously (see Table 1 for details). All experiments followed the same overall design template to probe the ventriloquism effect and the immediate aftereffect following established work (Wozny and Shams, 2011b; Park and Kayser, 2019, 2020, 2021; Park et al, 2021; Park and Kayser, 2022). Participants were adult volunteers who reported no history of neurological diseases, and normal vision and hearing.…”
Section: Methodsmentioning
confidence: 99%